A RECENT REVIEW ON ETHNOMEDICINAL, PHYTOCHEMICAL, AND PHARMACOLOGICAL ACTIVITIES OF MAJOR ASTRACEAE FAMILY PLANTS IN THE MĂCIN MOUNTAIN NATIONAL PARK, ROMANIA - AHMED A. ZEINHOM; RODICA MIHAELA DINICA; MARIANA LUPOAE; FANICA BALANESCU; ANDREEA NISTOR; ANNA BUSUIOC; ANDREEA BOTEZATU; BIANCA FURDUI; CATERINA DUMITRU (Scientific Study & Research: Chemistry & Chemical Engineering, Biotechnology, Food Industry, 2025)
Măcin Mountain National Park is a large, protected area in Tulcea County, Dobrogea, Romania. This park represents Romania's ancient geological, scientific, and archaeological sites, making it one of the top-ranked tourist destinations in the country. On this small territory (0.05 % of the country's surface), and in an area of 11,000 hectares, more than half of the Romanian flora can be found. This region stand out by its impressive fauna and flora. 72 plant species are protected as vulnerable and rare species, and 27 species are considered endemic plants. The purpose of this work is to evaluate the most recent and significant reports from literature data with regards to plants from Asteraceae family. Thus, the focus was on analyzing the importance of these species in traditional phytotherapy and modern medicine. Emphasis was given to biological properties, which were validated through scientific research. Consequently, multiple cosmetology and food industry applications were highlighted. Last but not least, studies concerning the safety uses and biotechnological research were presented.